Lymphoma-Associated Monoclonal Cryoglobulinemic Glomerulonephritis and Relationship with Hepatitis C Virus Infection: A Case Report. (18th August 2019) - Mutnuri, Sangeeta; Kassem, Hania; Badalamenti, John; Qian, You-Wen; Marquez, Christopher; Afrouzian, Marjan
Abstract : We report a case of type I cryoglobulinemic glomerulonephritis in a patient with chronic hepatitis C who presented with acute renal failure. The renal biopsy revealed membranoproliferative GN (MPGN) due to cryoglobulinemia with unexpected monoclonal Kappa restriction on immunofluorescence microscopy, suggesting an underlying hematopoietic malignancy. The bone marrow biopsy revealed presence of marginal zone lymphoma. Our case raises awareness regarding possibility of monoclonality in the renal biopsy of HCV-infected patients and exemplifies the crucial role the renal biopsy plays in detecting lymphoid malignancies where clinical features are ambiguous.